Analisis Komparasi Kinerja Keuangan Sebelum, Saat Terjadi Dan Sesudah Terjadi Pandemi Covid-19 Pada Sektor Food And Beverage Yang Terdaftar Pada BEI - Andryana, Sylvia; Widayanto, Eko A (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to analyze the financial performance of PT. Sarimelati Kencana Tbk before, during, and after the COVID-19 pandemic, covering the period from 2019 to 2023. The research method used is quantitative descriptive with a comparative approach, analyzing financial ratios such as liquidity, solvency, activity, profitability, and market value. The results show that in 2019, before the pandemic, the company's financial performance was stable. However, during the pandemic period (2020-2022), financial performance experienced significant decline, despite a temporary increase in 2021 due to innovations in selling pizza at strategic locations with promotional prices. In 2022, performance declined again, and post-pandemic (2023), the company has not yet stabilized its finances, as evidenced by decreases in profitability and market value ratios. The conclusion of this study is that the COVID-19 pandemic had a significant negative impact on the financial performance of PT. Sarimelati Kencana Tbk, and the company needs to implement more effective strategies to recover its performance post-pandemic.